A CYTOTOXIC PYRANONAPHTHOQUINONE FROM CULTURED LICHEN MYCOBIONTS OF HAEMATOMMA sp - Takenaka, Yukiko; Mizushina, Yoshiyuki; Hamada, Nobuo; Tanahashi, Takao (Heterocycles, 2017)
Spore-derived mycobionts of the lichen Haematomma sp. were cultivated on malt-yeast extract medium supplemented with 10% sucrose to produce a new pyranonaphthoquinone, 4, as well as two known compounds (-)-usnic acid (2) and 5-deoxy-7-methylbostrycoidin (3). The structure of 4 was determined by spectroscopic methods. The inhibitory activities of 3, 4, and 6-8 against mammalian DNA polymerases (pols) and cytotoxic effects against a HeLa human cervical cancer cell line were also evaluated. Compound 4 showed the strongest mammalian pol inhibitory activity and cytotoxicity (ID50 = 6.7 mu M) among the tested compounds.